2004
DOI: 10.1126/science.1098014
|View full text |Cite
|
Sign up to set email alerts
|

Increased Nuclear NAD Biosynthesis and SIRT1 Activation Prevent Axonal Degeneration

Abstract: Axonal degeneration is an active program of self-destruction that is observed in many physiological and pathological settings. In Wallerian degeneration slow (wlds) mice, Wallerian degeneration in response to axonal injury is delayed because of a mutation that results in overexpression of a chimeric protein (Wlds) composed of the ubiquitin assembly protein Ufd2a and the nicotinamide adenine dinucleotide (NAD) biosynthetic enzyme Nmnat1. We demonstrate that increased Nmnat activity is responsible for the axon-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
1,030
6
9

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 984 publications
(1,085 citation statements)
references
References 26 publications
40
1,030
6
9
Order By: Relevance
“…Indeed, potent therapeutic effects of resveratrol administration were reported in animal models of Alzheimer's disease and accelerated ageing [10,26,46], multiple sclerosis [47,48], Huntington's disease [9,49], Parkinson's disease [22,50], and even reducing peripheral axonal degeneration [51] or promoting functional recovery after traumatic spinal cord injury [23]. In this sense, resveratrol has been also reported to exert neuroprotection on in vitro models of ALS.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, potent therapeutic effects of resveratrol administration were reported in animal models of Alzheimer's disease and accelerated ageing [10,26,46], multiple sclerosis [47,48], Huntington's disease [9,49], Parkinson's disease [22,50], and even reducing peripheral axonal degeneration [51] or promoting functional recovery after traumatic spinal cord injury [23]. In this sense, resveratrol has been also reported to exert neuroprotection on in vitro models of ALS.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that increased dosage of key enzymes for mammalian NAD + -biosynthesis increase total cellular NAD + -levels and enhance the transcriptional regulation activity of a mouse Sir2 orthologue (Revollo et al, 2004). Such a strategy was shown also to protect injured axons in a SIRT1-dependent fashion in a Wallerian degeneration model (Araki et al, 2004). These studies suggest that mammalian Sir2 orthologues are sensitive to metabolic pathways that regulate the levels of NAD + .…”
Section: Molecular Links Of Cr and Aging Molecular Links Of Cr And Agmentioning
confidence: 96%
“…2) (Wolkow et al, 2000;Hertweck et al, 2004). When central members of the insulin-/ IGF-1 pathway, such as DAF-2 or AGE-1 lose their function due to mutations, life span in C. elegans is increased two-fold as compared to wild-type animals (Kenyon et al, 1993;Araki et al, 2004). Animals with weak alleles of the age-1 and daf-2 genes can bypass dauer formation as a non-feeding, stress-resistant larval state that allows dispersal under adverse conditions, and turn into long-living adults in a daf-16 dependent manner (Kenyon et al, 1993;Barbieri et al, 2003 Recent studies show that sirtuins do interfere with the insulin/ IGF-1 signaling pathway.…”
Section: Molecular Links Of Cr and Aging Molecular Links Of Cr And Agmentioning
confidence: 99%
“…Published evidence suggests that SirT1 prevents ageassociated diseases such as metabolic disorders (Picard et al, 2004;Kitamura et al, 2005;Moynihan et al, 2005;Bordone et al, 2006;Gerhart-Hines et al, 2007;Rodgers and Puigserver, 2007), neurodegenerative diseases (Araki et al, 2004;Parker et al, 2005;Chen et al, 2005a;Qin et al, 2006;Kim et al, 2007) and atherosclerosis . Accumulating evidence also point to SirT1 as having a function in cancer; however, inferences from the literature are that SirT1 has both oncogenic and tumor-suppressor activities.…”
Section: Introductionmentioning
confidence: 99%